2007
DOI: 10.1097/mao.0b013e31814619bd
|View full text |Cite
|
Sign up to set email alerts
|

Does Packing the Eustachian Tube Impact Cerebrospin al Fluid Rhinorrhea Rates in Translabyrinthine Vestibular Schwannoma Resections?

Abstract: Cerebrospinal fluid leak rates were similar in patients undergoing TL, SO, and MCF approaches, and CSF rhinorrhea was not decreased by ET packing. Patients whose ETs are packed with Proplast are at risk for extrusion and otorrhea years after their initial VS resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Many techniques have been described for reducing the incidence of CSF leakage: (1) tight suture of the cerebral dura mater closure area; (2) packing of the mastoidectomy defect with several strips of autologous abdominal fat graft tissue [33], or with other materials, such as polymethylmethacrylate, acrylic [34], and hydroxyapatite cement and titanium mesh [35], and (3) occlusion of the antrum, vestibulum, petrosal air cells, and Eustachian tube with bone wax [36,37]. According to our experience, middle ear exclusion is also an important precaution to avoid CSF leakage in case of highly pneumatized temporal bone.…”
Section: Discussionmentioning
confidence: 99%
“…Many techniques have been described for reducing the incidence of CSF leakage: (1) tight suture of the cerebral dura mater closure area; (2) packing of the mastoidectomy defect with several strips of autologous abdominal fat graft tissue [33], or with other materials, such as polymethylmethacrylate, acrylic [34], and hydroxyapatite cement and titanium mesh [35], and (3) occlusion of the antrum, vestibulum, petrosal air cells, and Eustachian tube with bone wax [36,37]. According to our experience, middle ear exclusion is also an important precaution to avoid CSF leakage in case of highly pneumatized temporal bone.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature perpetuates the existing discord, as the efficacy of ET obliteration is inconsistent from one study to another. Whereas some have shown that a meticulous enlarged translabyrinthine approach [8,9] or a Palva flap technique [10] have the potential to reduce CSF leaks, others report no difference in CSF rhinorrhea rates even though they obliterated the ET [28] . In our previous study, we found a statistically significant decrease in the rate of CSF leaks in patients who had undergone ET obliteration as compared to people who did not [22] .…”
Section: Discussion Eustachian Tube Obliterationmentioning
confidence: 99%
“…Although the injured eustachian tube can be plugged off to prevent the paradoxical CSF rhinorrhea, several other side effects in relation to the acoustic conductance and middle-ear mucus retention have been reported, reflecting the physiological compromise of this conduit. 26,27 In addition, there remains a cohort of cases in which the surgical endeavors such as packing the eustachian tube, fail to prevent the CSF rhinorrhea. 27 The present microanatomical study was thus guided by the philosophy of preserving the physiological integrity of anatomical structures as much as possible.…”
Section: Glasscock To Rhomboid or Rhomboid To Glasscock?mentioning
confidence: 99%
“…26,27 In addition, there remains a cohort of cases in which the surgical endeavors such as packing the eustachian tube, fail to prevent the CSF rhinorrhea. 27 The present microanatomical study was thus guided by the philosophy of preserving the physiological integrity of anatomical structures as much as possible. The mean distance from the medial carotid wall midpoint to the medial-most point on the eustachian tube, in our study was 6.35 AE 0.58 mm (range, 5.4 to 7.1 mm) ( Table 1).…”
Section: Glasscock To Rhomboid or Rhomboid To Glasscock?mentioning
confidence: 99%